Impact of botanical extracts on mungbean pest management and seed storability in the northern highlands of Tanzania - Kessy, Godfrey Adolph; Mkindi, Angela; Binagwa, Papias; Ndakidemi, Patrick Alois (Frontiers in Sustainable Food Systems, 2024)
This study assessed the efficacy of plant extracts as alternatives to synthetic pesticides for pest control and seed quality preservation in mungbean cultivation in northern Tanzania, specifically at TARI Selian and Miwaleni. The study employed a randomized complete block design. Four plants’ extracts—Tephrosia vogelii, Clutia abbsynica, Clausena anisata, and Lobelia gibelloa—were evaluated during the 2020 growing season (field) and 2021 storage period (storability). The study focused on their effects on insect pests (leaf beetles, thrips, aphids, whiteflies, and pod borers) and their ability to maintain seed quality during storage. C. anisata emerged as the most effective extract across all pests, demonstrating high suppression rates for thrips (3.4), aphids (3.22), whiteflies (3.4), and pod borers (2.7). In contrast, L. gibelloa was the least effective, with lower suppression rates for thrips (3.1) and aphids (3.1). Furthermore, botanical treatments significantly reduced pest damage in stored seeds, with T. vogelii and C. abbsynica showing superior performance in preserving seed weight and quality during storage. Seeds treated with T. vogelii had significantly fewer holes and lower weight loss compared to other treatments, indicating its effectiveness in both pest management and seed preservation. Conversely, L. gibelloa and C. anisata contributed to greater weight loss, particularly at higher application rates. The study demonstrates that plant extracts can offer a sustainable, eco-friendly alternative to synthetic pesticides, effectively controlling pests and preserving seed quality. These findings are crucial for improving mungbean production and storage, enhancing food security, and reducing reliance on chemical pesticides in diverse agro-ecological contexts. Future research should further explore the long-term ecological impacts and optimal application rates of these botanicals for integrated pest management and seed storage.